High Mobility Group Box 1 (HMGB1) Activates an Autophagic Response to Oxidative Stress - Tang, Daolin (Mary Ann Liebert, Inc., 2011)
AIMS: Autophagy, the process by which cells break down spent biochemical and damaged components, plays an important role in cell survival following stress. High mobility group box 1 (HMGB1) regulates autophagy in response to oxidative stress. RESULTS: Exogenous hydrogen peroxide (H(2)O(2)) treatment or knockdown of the major superoxide scavenger enzyme, superoxide dismutase 1 (SOD1), by small interfering RNA (siRNA) increases autophagy in mouse and human cell lines. Addition of either SOD1 siRNA or H(2)O(2) promotes cytosolic HMGB1 expression and extracellular release. Importantly, inhibition of HMGB1 release or loss of HMGB1 decreases the number of autophagolysosomes and autophagic flux under oxidative stress in vivo and in vitro. INNOVATION: HMGB1 release may be a common mediator of response to oxidative stress. CONCLUSION: HMGB1 is important for oxidative stress-mediated autophagy and serves as a new target for the treatment of stress-associated disorders. Antioxid. Redox Signal. 15, 2185–2195.